Acoustical and thermal characterization of sustainable materials derived from vegetable, agricultural, and animal fibers. (February 2022) - Bousshine, Said; Ouakarrouch, Mohamed; Bybi, Abdelmajid; Laaroussi, Najma; Garoum, Mohammed; Tilioua, Amine
Abstract: Sustainable materials tend to become an alternative to synthetic materials in the building sector for acoustical correction and thermal insulation. This research work is dedicated to the acoustical and thermal characterization of some sustainable materials derived from vegetable, agricultural, and animal wastes, i.e. date palm (trunk, petiole, pinnate leaves, bunch, and fiber mesh), reed, esparto, olive tree, fig tree, wood sawdust, chicken feathers, and sheep wool. All materials are characterized experimentally using standard methods: impedance tube and guarded hot plate for absorption coefficient and thermal conductivity measurements, respectively. The results indicate that the majority of studied materials exhibit good acoustical and thermal performances: absorption coefficient in the range 0.6–0.9 (medium frequencies) and thermal conductivity between 0.044 and 0.091 W/m.K. It is found that esparto, petiole, chicken feathers, and sheep wool meet the main properties required for acoustic correction and thermal insulation applications and have great potential to replace synthetic materials (glass wool: 0.95, 0.044 W/m.K). The measured absorption coefficient and thermal conductivity were (0.9, 0.065 W/m.K); (0.88, 0.072 W/m.K); (0.94, 0.045 W/m.K); (0.95, 0.044 W/m.K); for esparto, petiole, chicken feathers, and sheep wool, respectively.